1998
DOI: 10.1021/bi980506i
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Zinc-Dependent β-Lactamase from Bacillus cereus at 1.9 Å Resolution:  Binuclear Active Site with Features of a Mononuclear Enzyme,

Abstract: The structure of the zinc-dependent beta-lactamase II from Bacillus cereus has been determined at 1.9 A resolution in a crystal form with two molecules in the asymmetric unit and 400 waters (space group P3121; Rcryst = 20.8%). The active site contains two zinc ions: Zn1 is tightly coordinated by His86, His88, and His149, while Zn2 is loosely coordinated by Asp90, Cys168, and His210. A water molecule (W1) lies between the two zinc ions but is significantly closer to Zn1 and at a distance of only 1.9 A is effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
320
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(344 citation statements)
references
References 39 publications
22
320
1
1
Order By: Relevance
“…We solved the X-ray structure of M5 [supporting information (SI) Table S1], which showed that none of these mutations entails changes in the global fold (0.6 Å rmsd on all nonhydrogen atoms vs. wt BcII). The active site of BcII can be described as a shallow groove flanked by loops L3 and L10, hosting 2 Zn(II) ions located in its floor, which is defined by loops L7, L9, and L12 (20,21) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We solved the X-ray structure of M5 [supporting information (SI) Table S1], which showed that none of these mutations entails changes in the global fold (0.6 Å rmsd on all nonhydrogen atoms vs. wt BcII). The active site of BcII can be described as a shallow groove flanked by loops L3 and L10, hosting 2 Zn(II) ions located in its floor, which is defined by loops L7, L9, and L12 (20,21) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The structure of di-Zn(II) BcII from B. cereus [PDB ID code 1BC2 (20)] was selected as the reference starting structure for all our calculations, as reported in ref. 41.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this heterogeneity, M␤Ls have been classified into three subclasses: B1, B2, and B3 (3). Subclass B1 includes several chromosomally encoded enzymes, such as BcII from Bacillus cereus (11)(12)(13), CcrA from Bacteroides fragilis (14 -17), BlaB from Elizabethkingia meningoseptica (18), and transferable VIM (19), IMP (20,21), SPM (22), and GIM (23) type enzymes. Subclass B2 includes the CphA (24,25) and ImiS (26) lactamases from Aeromonas species and Sfh-I from Serratia fonticola (27).…”
mentioning
confidence: 99%
“…Considerable information exists regarding the B1 and B3 enzymes, including X-ray diffraction (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), spectroscopic (9,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), mechanistic (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and computational studies (60)(61)(62)(63)(64)…”
mentioning
confidence: 99%